The development of reflective skills in physical education teacher education: a systematic review - Eugénia Lopes Azevedo; Isabel Ribeiro Mesquita; Rui Flores Araújo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Research has shown an increased attention towards Reflective Practice as a successful aspect in the professional development of Physical Education Teacher Education. Notwithstanding, there is a lack of empirical research about how teachers’ reflective skills should be developed in this context. The aim of this systematic review was to understand what and how has been studied about physical education teachers’ reflective skills, and how such strategies can be further developed and refined in Physical Education Teacher Education. Following Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) (Page et al., 2021) six databases were included to ensure that all relevant data was considered, and criteria scales were adapted in order to access studies’ quality. The results show the importance of incorporating meticulously planned and organized practicum in teachers’ training of reflective skills. Despite the importance of collaborative work in reflective skills development, there is a need to perform a deeper examination of those which contribute to improve reflective skills and how teachers develop reflection in collaborative settings, such as through the examination of communities of practice. Besides, writing reflections and video-taped classroom situations can enhance teachers’ reflective skills, although supervision is required. This review highlights the important yet challenging role of teachers’ reflective skills investigation, in order to achieve a deeper understanding of the contexts and strategies through which this issue is developed.